Silica Extracts from Fly Ash Modified Via Sol-Gel Methods and Functionalized with Cmpo for Potential Scavenging of Rare Earth Elements La³⁺ and Ce³⁺ - Pizarro-Konczak, J; Ortiz-Calderon, C; Gómez-Barrena, M; Diaz-Navarro, C (Elsevier Ltd, 2024)
A mesoporous material was synthesized using silica extracts from fly ash and its properties were studied. Subsequently, it was functionalized with carbamoylmethylphosphine oxide (CMPO) to capture La3+ and Ce3+. The developed mesoporous material was obtained by the sol-gel method and was called Si-MMS (siliceous mesoporous materials), subsequently functionalized with APTMS (1-(2-aminoethyl)-3-aminopropyl trimethoxysilane) in a reflux system, which led to the synthesis of Si-MMS-APTMS. This derivative was modified with carbonyldiimidazole (CDI) and diethylphosphonoacetic acid, which finally resulted in the synthesis of Si-MMS-CMPO as the final product. The materials were characterized by DRIFT, XRD, SEM-EDS, TEM, XPS, elemental analysis and nitrogen isotherms at −196 °C, confirming that the synthesis and subsequent modification of the mesoporous structure was successful. Adsorption studies in batch systems indicated that the optimal pH for La3+ was 6, the Langmuir isotherm model and the non-linear Sips models were perfectly fitted and the best fitting kinetics is the Elovich model. For Ce3+ the optimal pH was 7.5, the non-linear Sips isotherm fit the best and the non-linear Pseudo-second order kinetics was the mechanism that best represents the adsorption. The maximum experimental adsorption capacity qe of La3+ was 17.00 mg g−1 and for Ce3+ was 30.09 mg g−1. In both cases, the rapid adsorption suggests an open porous matrix that facilitates the formation of chelates between the adsorbates and the phosphoryl group -PO32-. © 2024 Elsevier B.V.